Vascular Stent Fracture and Migration to Pulmonary Artery during Arteriovenous Shunt Thrombectomy. Issue 2 (April 2013) - Ho, Jessica M.; Kahan, Jonathan; Supariwala, Azhar; Silberzweig, James; Kornberg, Robert; Swistel, Daniel; Dreifuss, Ronald
Purpose: Endovascular stent fracture and migration is an extremely rare complication of arteriovenous shunt thrombectomy. Technique: We report a case of endovascular stent fracture following repeat arteriovenous graft thrombectomy, which was complicated by migration of a 26 millimeter stent fragment to the left main pulmonary artery. Attempts at percutaneous transvenous retrieval were unsuccessful, and an open thoracotomy to extract the stent fragment was performed. Conclusions: Although there is no consensus for the management of endovascular stents that have migrated to the pulmonary arteries, stent retrieval may be necessary in cases where arterial flow is compromised or heavy clot burden is a concern. Moreover, steps toward prevention of stent fracture and migration should be considered in order to preclude such occurrences – avoidance of puncturing the stent for hemodialysis access, discontinuation of use of the Arrow-Trerotola device through or near stents, and consideration of short segment angioplasty for regional intrastent stenosis rather than typical long segment venous angioplasty.